Mathematical approaches for powders and multiparticulate units processability characterization in pharmaceutical development - Vasiljević, Ivana; Turković, Erna; Aleksić, Ivana; Parojčić, Jelena (Archives of Pharmacy, 2022)
An understanding of material properties and processing effects on solid dosage forms performance is required within the Quality-by-design approach to pharmaceutical development. Several research groups have developed mathematical approaches aiming to facilitate the selection of formulation composition and the manufacturing technology. These approaches are based on material particulate, bulk and compression-related properties. This paper provides theoretical assumptions and a critical review of different mathematical approaches for processability characterization of powders and multiparticulate units. Mathematical approaches have mainly been developed for directly compressible materials, but sometimes other manufacturing technologies, such as roller compaction and wet granulation, are also considered. The obtained compact tensile strength has been implemented in the majority of approaches, as an important characteristic describing compact mechanical properties. Flowability should be also evaluated, since it affects sample processability. Additionally, particle size and shape, material density and compressibility, compactibility and tabletability profiles have been also distinguished as relevant properties for solid dosage form development. The application of mathematical approaches may contribute to the mechanistic understanding of critical material attributes and facilitate dosage form development and optimization. However, it is essential to select the appropriate one, based on the intended dosage form characteristics, in order to ensure that all relevant powder/multiparticulate units characteristics are implemented and critically evaluated.